The Effect of Leadership Style and Organizational Culture Toward Teacher Motivation of MTs Arrohman Jombang in Academic of 2016/2017 - Khudriyah Khudriyah (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2017)
Leadership style and organizational culture in an organization has big effect toward the growth of employee motivation to work. In education as well as, the school leadership style and organizational culture have influence of teachers’ motivation in conducting their tasks. The study is aimed to describe how far the school leadership style and organizational culture influence teachers’ motivation to work at MTs Arrohman Jombang. This study is quantitative and questionnaire as the instrument. The result shows that the leadership style and organizational culture partially or simultaneously influence significantly on the teachers’ motivation in MTs Arrohman Jombang in academic year of 2015/2016 proved by t-test results t test > t table (3,358 > 2,023) with a significant level of t < 5% (0,002 < 0,05) and Ftest of 79,228 and a significance level of F < 5% (0.000 <0,05). Whereas, the influence of variables of leadership style and organizational culture on the teachers’ motivation was 80,2% and the rest of 19,8% is influenced by other factors